Batch-to-batch consistency trial of an adenovirus type-5 vector-based COVID-19 vaccine in adults aged 18 years and above. (2nd December 2022) - Li, Zhuo-Pei; Shi, Yun-Feng; Hou, Li-Hua; Jin, Peng-Fei; Ma, Shi-Hua; Pan, Hong-Xing; Zhang, Jin-Long; Shan, Yong-Mei; Huang, Hai-Tao; Wu, Shi-Po; Du, Pan; Wang, Xue; et al.
ABSTRACT: Background: The demonstration of batch-to-batch consistency is indispensable for quality control of vaccines. Methods: We conducted a randomized, double-blind, parallel-controlled trial to evaluate the immunogenicity consistency of a single shot of Ad5-nCoV in healthy adults who had not previously received any COVID-19 vaccine. All eligible participants were randomly assigned equally to receive one of the three consecutive batches of Ad5-nCoV (5 × 10 10 viral particles/vial, 0.5 mL). The primary endpoint was geometric mean titers (GMTs) of serum SARS-CoV-2 receptor-binding domain (RBD)-specific IgG on day 28 post-vaccination. Results: One thousand fifty participants were enrolled, with 350 (33%) participants per group. On day 28 post-vaccination, GMTs in three groups were 78.3 binding antibody units (BAU)/mL (95% CI 70.3–87.3), 82.9 BAU/mL (73.9–92.9), and 78.8 BAU/mL (70.2–88.4), respectively. The two-sided 95% CIs for the GMT ratios between each pair of batches were all between 0.67 and 1.5. The highest incidence of solicited adverse reactions within 7 days post-vaccination was reported by batch 3 recipients (23.1% versus 15.1% in batch 1 recipients and 14.6% in bath 2 recipients; p = 0.0039). None of the serious adverse events were related to vaccination. Conclusions: Immunogenicity consistency between consecutive batches of Ad5-nCoV was well established in adults. Clinical trial registration: This trial was registered with ClinicalTrials.gov (NCT05313646).